International financial reporting standards adoption and accounting quality: Evidence from Ghanaian listed firms - Yeboah, B.; Pais, C. (Afro-Asian Journal of Finance and Accounting, 2021)
The adoption of International Financial Reporting Standards (IFRS) by Ghanaian listed firms form the basis of higher accounting quality and reliability of accounting information from IFRS application. Existing literature suggests that the adoption affects the level of accounting quality. The aim of this paper is to examine whether the shift to IFRS minimises weaknesses in Ghana National Accounting Standards (GNAS) in measuring accounting quality. The paper employs research design metrics of discretional accruals, accrual quality, earnings smoothness, small loss avoidance and price-earnings to compute accounting quality of Ghana Stock Exchange (GSE) firms. The results suggest that accounting quality has improved after the shift to IFRS. This research fills the gap in Ghana level, given that there was no such study. Also, this study gives evidence of improvement in the information environment of GSE capital market after the shift in terms of information quality and accounting comparability.